Andy Pandy : Ball of String - BBC (London, United Kingdom BBC Children's Books, 2002)
How to be a Gardener is the BBC's most ambitious gardening project ever. Led by Alan Titchmarsh it includes eight hours of primetime television and two major hardback books. There's no great mystery to being a successful gardener - most of it is just plain common sense - but an appreciation of the natural world at work in our gardens will certainly help. The culmination of years of experience, Alan has distilled his knowledge and passion for the subject into the two volumes of How to be a Gardener. In Book 1 he sets out the basic principles of gardening to provide a complete reference manual for any garden owner.
Keywords: Read Aloud -- Read Aloud